2020
DOI: 10.5999/aps.2019.00962
|View full text |Cite
|
Sign up to set email alerts
|

The suprafascial course of lower leg perforators: An anatomical study

Abstract: Background Perforator mapping has been well described in the literature. Once the suprafascial plane is reached, the course of perforators is considered constant. However, the surgeon must be aware of whether an anastomosis exists between perforators superficially to the fascia, in order to choose the best vessel upon which to base the reconstruction. Our retrospective in vivo anatomical study of lower leg perforator flaps presents the first description of variations in the suprafascial path of perforators, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…55,[57][58][59] Perforators often follow a variable course on their route to the skin once piercing the deep fascia. 4,60 It is therefore critical to map the route of the perforator. This significantly speeds up recipient dissection and avoids inadvertent injury to the vessels.…”
Section: Perforator Mappingmentioning
confidence: 99%
“…55,[57][58][59] Perforators often follow a variable course on their route to the skin once piercing the deep fascia. 4,60 It is therefore critical to map the route of the perforator. This significantly speeds up recipient dissection and avoids inadvertent injury to the vessels.…”
Section: Perforator Mappingmentioning
confidence: 99%
“…4 5 The suprafascial architecture of perforators and sub-branches may now be assessed in real-time imaging. 6 7 Applying correct settings, modern standard devices are capable to detect vessels of 0.2 mm and less in diameter. 5 8 9 Anatomic and hemodynamic data may be provided in real-time imaging by CCDS of both, vascular structures of the donor and recipient sites of flap reconstructions.…”
mentioning
confidence: 99%
“…5 8 9 Anatomic and hemodynamic data may be provided in real-time imaging by CCDS of both, vascular structures of the donor and recipient sites of flap reconstructions. 6 10 Besides qualitative parameters as number and precise location of microvessels, quantitative parameters as vessel diameter and B-Flow velocities may be measured for a better comprehension of perforator flap physiology. Flow direction of arterial and venous vascular structures, turbulences, and muscular/subcutaneous course can be assessed and visualized.…”
mentioning
confidence: 99%
“…It passes between the two heads of the tibialis posterior and enters the extensor compartment, crossing the interosseous membrane. Along its course, the ATA gives out 3–4 perforators on average, both musculocutaneous and septocutaneous [ 7 , 8 ]. Morrison and Shen [ 9 ] demonstrated that in most cases the main perforator is a septocutaneous vessel that originates within 7 cm from the fibular head and penetrates the deep fascia through the anterior intermuscular septum between the extensor digitorum longus and peroneus muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Doppler ultrasonography is the cornerstone of perforator flap surgery; perforators are identified during the pre-operative planning guide flap design, as well as during the surgical approach. Having great accuracy during pre-operative planning saves time, eases flap elevation and may help in avoiding unnecessary exploration [ 8 ]. We place great emphasis on getting to know perforators blood flow variations to ensure the best surgical outcome with no complications.…”
Section: Introductionmentioning
confidence: 99%